2007
DOI: 10.1017/s0007114507336830
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of flavoneC-glucosides andp-coumaric acid from antioxidant of bamboo leaves (AOB) in rats

Abstract: The metabolism of flavone C-glucosides and p-coumaric acid from antioxidant of bamboo leaves (AOB) in rats is discussed systematically in the present study. Following single oral administration of AOB, p-coumaric acid was detected in plasma but not in gastrointestinal tract extracts and faeces, and the corresponding absorption pharmacokinetic curve at different time points showed a prolonged elimination phase with p-coumaric acid being detected in the kidneys and excreted as its original form (1·80 (SD 0·24) %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 31 publications
4
59
0
2
Order By: Relevance
“…In agreement with our results, Lee et al (2008a) also demonstrated that bamboo culm extract supplementation in mice fed an atherogenic diet significantly reduced the levels of thiobarbituric acid reactive substances and protein carbonyls, suggesting a protective effect of bamboo culm extract supplementation against lipid peroxidation and protein oxidation (Lee et al, 2008a). Results of a feeding test in vivo also showed that the anti-oxidants of bamboo leaves could significantly improve the activities of T-SOD and GPx (Zhang et al, 2007). But in the present study, it seems that BLE had no effect on the activity of T-SOD.…”
Section: Discussionsupporting
confidence: 84%
“…In agreement with our results, Lee et al (2008a) also demonstrated that bamboo culm extract supplementation in mice fed an atherogenic diet significantly reduced the levels of thiobarbituric acid reactive substances and protein carbonyls, suggesting a protective effect of bamboo culm extract supplementation against lipid peroxidation and protein oxidation (Lee et al, 2008a). Results of a feeding test in vivo also showed that the anti-oxidants of bamboo leaves could significantly improve the activities of T-SOD and GPx (Zhang et al, 2007). But in the present study, it seems that BLE had no effect on the activity of T-SOD.…”
Section: Discussionsupporting
confidence: 84%
“…Zhang et al (2007) observed a decline in total C-glycosyl flavone presence in the total gastrointestinal contents of rats from 83 ± 1 % at 30 min to 52 ± 1 % at 12 hr following oral administration of a bamboo leaf extract containing orientin, isoorientin, vitexin and isovitexin. This decline was not accompanied by the presence of these compounds in the urine or plasma of these animals, indicating that absorption was not wholly responsible for this effect, but was allied to increased concentrations of small aromatic products of microbial flavonoid metabolism.…”
Section: The Biological Fate Of C-glycosyl Flavonoids In the Human Dietmentioning
confidence: 91%
“…Despite these findings, the authors of a similar study reported the absence of C-glycosyl flavonoids in the collected urine or plasma of Sprague Dawley rats (n = 4) at any point in the 72 hr following a high, single-dose oral administration of 1 g kg -1 bamboo leaf extract in water (100 mg ml -1 ) containing the four flavone C-glycosides orientin, isoorientin, vitexin and isovitexin. Similarly, none of these compounds were detected in the excised liver, brain, thigh muscle and kidney tissue of these animals, prompting the authors to conclude that C-glycosyl flavones are not readily absorbed in the small intestine (Zhang et al, 2007). In this case, it is highly likely that the HPLC-DAD methodology used for the analysis of these samples did not provide sufficient sensitivity in the detection of these compounds however, nor was provision made for the hydrolysis of metabolic conjugates prior to analysis of parent structures.…”
Section: The Biological Fate Of C-glycosyl Flavonoids In the Human Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…W badaniach [15,16,26] potwierdza się, że ze względu na małą masę cząsteczkową kwasy ferulowy i p-kumarowy są częściowo wchłaniane z przewodu pokarmowego w niezmienionej postaci. Mogą być transportowane z żo-łądka, gdyż niskie pH żołądka ułatwia transport tych związków w formie niezdysocjowanej poprzez mechanizm dyfuzji biernej.…”
Section: Wyniki I Dyskusjaunclassified